Pengembangan Media Infografis Interaktif Berbasis Discovery Learning Pada Materi Energi Terbarukan Untuk Siswa SD - Raini Marita; Deris Stiawan; Makmum Raharjo (Jurnal Penelitian Pendidikan IPA, 2025)
The limitations of visual learning media that are appropriate for the characteristics of elementary school students have an impact on the low level of understanding of abstract science material, such as renewable energy. In the context of the need for a learning approach that supports active engagement and visualization, this study aims to develop interactive infographic media based on Discovery Learning for renewable energy materials for sixth-grade elementary school students. This study employs the Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. Validation was conducted by experts in media, language, and content, while practicality and effectiveness were tested through limited trials and field tests involving teachers and students at SD Negeri 1 Pagar Kaya. The results of the study indicate that the developed media meet the criteria for high validity (average >85%), high practicality (average >90%), and effectiveness (N-Gain = 0.72) in enhancing students' understanding. The interactive infographic media developed facilitates the discovery-based learning process in a visual and engaging manner, encouraging students to actively explore concepts related to renewable energy. This study confirms that the integration of interactive visual design and the Discovery Learning approach can be an effective strategy for developing digitally based science learning media at the elementary level.